Implementasi Pojok Literasi Dalam Meningkatkan Minat Baca Siswa Di SDN 5 Kelapa - Yulyanah, Siti; Fadia, Asti Nur; Mutiara RKJ, Rani Regita; Fikri, Mohamad (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
In line with the development of increasingly sophisticated times, reading has become an important thing, the activity of reading has many meanings in human life because by reading a person can understand and apply something. Reading is the process of absorbing knowledge through reading or writing. However, based on observations and discussions with the community, it was discovered that there were still limitations for female students in accessing varied and educational reading books at SDN 5 Kelapa, Kelapa sub-district, West Bangka district, Bangka Belitung archipelago. This has the potential to hinder their literacy development, which in turn can affect academic achievement and general cognitive development. Therefore, through the IAIN KKN Syaikh Abdurrahman Siddik Bangka Belitung student community service program in 2024, group 09 created a literacy corner as an effort to foster interest in reading among elementary school students. The literacy corner is one step in fostering interest in reading at elementary school level, which functions as a provider of reading materials, knowledge and information for students. By utilizing an attractively decorated corner of the room to serve as a book collection place. It is hoped that this literacy corner can stimulate students to be more interested in reading and doing other activities that can develop their potential and thinking power. The aim is to cultivate interests and habits of cultivating interests and reading habits, especially through books with a visual approach. Based on the results of the implementation of the literacy corner at SDN 5 Kelapa, it shows that the literacy corner program is effectively used in increasing students' interest in reading. The enthusiasm of the school and students in the process of creating a literacy corner has motivated the creation of a literacy corner in every classroom.